Dragonfly Genera of the New World: an illustrated and annotated key to the Anisoptera - Pessacq, Pablo (2008)
The Neotropical region, with more than 1,600 described species, hosts the largest biodiversity of Odonata in the world (Garrison 1991, Tsuda 2000), reaching its maximum expression in central and northern South America. While North American Odonata has been well surveyed (if not completely) and several compilations and field guides exist (Westfall & May 1996, Dunkle 2000, Biggs 2004), the opposite rules in Central and South America. Even when a wide number of species have been described in the last years, many more are still waiting to be discovered and no general keys or compilations for this region exist (with the exceptions of Borror 1945 and Munz 1919). In addition, Neotropical Odonata bibliography is widely scattered.